Dissemination of precision farming in Germany: acceptance, adoption, obstacles, knowledge transfer and training activities - Reichardt, M; Jürgens, C; Klöble, U; Hüter, J; Moser, K (Precision agriculture, 2009)
The adoption of precision farming (PF) was studied on the basis of personal interviews conducted at several agricultural exhibitions in Germany. Between 6.65% and 11% of the interviewed farmers used PF. The majority used data collection techniques such as GPS-based area measurement and soil sampling rather than variable rate application techniques such as site-specific sowing and fertilising. Roughly half the farmers interviewed knew about PF. About 7-10% of them intended to start using PF in the future. The results indicated that a large number of farmers did not even know what PF meant. In order to get more insight into this situation, several interviews were conducted with farmers already using PF techniques. A further study in 2005 of PF education in Germany indicated that, especially at vocational and technical schools, the subject was only covered to a small extent although the aim was to give a better coverage in future. At higher education levels, such as at universities and technical colleges, the teaching of PF was clearly better established. In order to promote awareness of PF among farmers, information and teaching materials adapted to the relevant educational levels were developed and tried out at training events. The main topics addressed were parallel tracking systems, site-specific nitrogen fertilising, yield mapping in grain production and the use of PDAs in crop farming. Finally, preliminary survey results are presented showing how knowledge about PF can best lead to its adoption and transfer into daily practice.